РУССКИЕ И ПОЛЬСКИЕ ЮМОРИСТИЧЕСКИЕ ЖУРНАЛЫ О ЗАВЕЩАНИИ ЛЬВА ТОЛСТОГО - Piotrowska, Joanna (Przegląd Rusycystyczny, 2016)
RUSSIAN AND POLIS H HUMOR MAGAZINES ON THE WILL OF LEO TOLSTOY Summary The article discusses publications concerning Leo Tolstoy’s will, which appeared soon after his death in Polish (“Mucha”, “Kolce”, “Nowy Szczutek”) and Russian (“Satirikon”, “Budilnik”) humor magazines. These publications focused on two topics — open letters by Lev Lvovich Tolstoy (the son of the writer accused Vladimir Chertkov of the death of his father and concealing the last version of the will from Tolstoy’s family) and plans for selling Yasnaya Polyana, which were described in the daily press. An analysis of publications shows that Polish humor magazines, like the Russian ones, judged the heir to Tolstoy’s property critically, but the criticism of Polish press was not as harsh. However, unlike Russian magazines, Polish periodicals clearly compared the writer with his mercantile sons and — which is interesting — with his wife. At the same time Polish opinion of the will as such was ambiguous. русские